Ohjelmistorobotiikan mahdollisuudet liiketoimintaprosessin kehittämisessä - Sälkiö, Johanna (2025)
Organizations continuously seek to improve and innovate their business processes to maintain efficiency and competitiveness. Robotic Process Automation (RPA) is one of the automation technologies that has significantly increased in recent years, allowing improvements in accuracy and quality, while freeing up human resources for more strategically important tasks. This master's thesis examines the possibilities of RPA in business process development. The aim of this research was to examine how RPA can be utilized in the development of business processes. The theoretical foundation of the study is based on a literature review, which discusses business processes and their mapping, as well as the benefits and requirements of RPA. The literature review deepens the understanding of the role of RPA in the development and optimization of business processes. The empirical part of the research was conducted as a case study, where data was collected through observations, document analysis, and interviews. The data was analyzed using thematic analysis, which allowed for the creation of a process diagram. The process diagram created based on the collected data provided a visual representation of the current state of the process, which helped identify the challenges of the process and the steps that could be automated. The study identified key area for development such as the lack of an overall view of the process stages, which complicates process management and optimization. Additionally, the amount of manual work was seen as overwhelming and was therefore another key area for development in the process. The study identified several steps that could be automated based on their regularity and repetition. Automating these steps can improve the efficiency of the process and shift employees' working time to more productive tasks.